Fenomena Buzzer dalam Cerpen "Riuh" Karya Okky Madasari: Analisis Wacana Kritis Teun A. van Dijk - Lusiana, Martha (LOKABASA, 2020)
The purpose of this study is to identify buzzer as a power-exercise phenomenon that has been narrated in Okky Madasariâ€™s short story entitled Riuh using the Socio Cognitive Approach by Teun A. Van Dijk. Within the conduct of the study, the note-taking technique had been adopted in order to classify the data in accordance to the social and power discourse that had been found. The data that had been collected data were analysed by using the Van Dijkâ€™s three-dimensional method namely: (a) text; (b) social cognitions: and (c) social context. The core of the Van Dijkâ€™s analysis is to combine the three dimensions into a complete and integrative analysis. Thus, the results of the analysis have uncovered three types of discourse. First, the buzzer has held the access to influence the discourse. Second, the power exercise has been identified between the buzzer and the ruling elites who are capable of funding the access toward the discourse. Third, it has been identified as well that the buzzer becomes the device for the political propaganda in the social media within the cases of corruption. At the end of the study, it is expected that the results of the study are able to contribute to the wide array of the studies on the Van Dijkâ€™s Critical Discourse Analysis.AbstrakTujuan penelitian ini adalah melihat buzzer sebagai fenomena praktik kekuasaan yang dinarasikan dalam cerpen "Riuhâ€ karya Okky Madasari dengan pendekatan kognisi sosial dari Teun A. van Dijk. Dengan menggunakan teknik catat, data diklasifikasi menurut wacana sosial dan kekuasaan yang berhasil ditemukan. Setelah itu, data tersebut dianalisis dengan menggunakan metode analisis tiga dimensi model van Dijk. Metode ini terdiri atas tiga dimensi/bangunan, yakni (a) teks, (b) kognisi sosial, serta (c) konteks sosial. Inti analisis van Dijk adalah menggabungkan ketiga dimensi wacana tersebut ke dalam satu kesatuan analisis yang utuh. Berdasarkan analisis, terdapat tiga wacana yang terungkap. Pertama, buzzer memiliki akses untuk memengaruhi wacana. Kedua, terungkap adanya praktik kekuasaan antara buzzer dan elite penguasa yang mampu membiayai akses wacana. Ketiga, ditemukan pula bahwa buzzer menjadi alat propaganda politik di media sosial dalam kasus korupsi. Penelitian kualitatif-deskriptif ini diharapkan dapat mempeluas kajian analisis wacana kritis menurut Teun. A. van Dijk.Â